2006
DOI: 10.1158/0008-5472.can-05-3951
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Active Origins of DNA Replication in Tumor versus Normal Cells

Abstract: Previously, a degenerate 36 bp human consensus sequence was identified as a determinant of autonomous replication in eukaryotic cells. Random mutagenesis analyses further identified an internal 20 bp of the 36 bp consensus sequence as sufficient for acting as a core origin element. Here, we have located six versions of the 20 bp consensus sequence (20mer) on human chromosome 19q13 over a region spanning f211 kb and tested them for ectopic and in situ replication activity by transient episomal replication assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 52 publications
5
33
0
Order By: Relevance
“…Indeed, increased activity of DNA replication origins in tumor cells or SV-40 transformed cells have been reported, suggesting that transformation may induce greater frequency of initiation of origins at certain loci. [39][40][41][42] The increased origin activity in tumor/transformed cells compared to normal cells may be influenced by many parameters including concentration and activity of initiation factors, chromatin structure and nuclear organization. 41 Potentially, FA proteins might be involved in these processes to regulate initiation of DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, increased activity of DNA replication origins in tumor cells or SV-40 transformed cells have been reported, suggesting that transformation may induce greater frequency of initiation of origins at certain loci. [39][40][41][42] The increased origin activity in tumor/transformed cells compared to normal cells may be influenced by many parameters including concentration and activity of initiation factors, chromatin structure and nuclear organization. 41 Potentially, FA proteins might be involved in these processes to regulate initiation of DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the origin activity in the tumor-transformed cells is two-to threefold higher than that of normal cells. 30 In chromosomal DNA replication, a plausible supermolecular assembly, the origin recognition complex, and the replisomes are thought to function in DNA replication initiation and the elongation of the DNA strands, respectively. The cell cycle starts from a Go quiescent state.…”
Section: Chromosomal Dna Duplication and Cell Divisionmentioning
confidence: 99%
“…A twofold increase in origin activity across the same 12.5 kb region of the human c-myc locus was also found in the isogenic cell lines WI38 and their transformed counterpart WI38 (SV40) [Tao et al, 2001], ruling out the possibility that cell type effects were the cause of the differential origin usage found in HeLa and NSF cells. It was thus concluded that the increased origin activities were the result of cellular transformation.More recent studies have found two-to threefold higher origin activities in transformed/tumor cells compared to normal cells, suggesting higher activation of these origins located across this $211 kb region on human chromosome 19q13 [Di Paola et al, 2006]. Again, use of the isogenic cell lines of WI38 and WI38(SV40) showed that the origins are at least twice as active in the transformed cell line (WI38(SV40)) compared to that of its normal counterpart (WI38), ruling out the possibility that cell type effects were responsible for increased frequency of initiation.…”
mentioning
confidence: 95%
“…The distribution of this 20mer consensus over 1 Mb of human chromosomal DNA is similar, quantitatively and qualitatively to the distribution of the ARS consensus sequence (ACS) on S. cerevisiae chromosomes . Finally, six versions of the 20mer which were analyzed ectopically and endogenously were found to act as origins of DNA replication in plasmids as well as in situ, at their chromosomal loci, suggesting that the 20-bp consensus sequence can be used to predict chromosomal regions that contain replication origins [Di Paola et al, 2006]. …”
mentioning
confidence: 99%
See 1 more Smart Citation